Contemporary world of education and challenges in the teacher-parent relationship - Mędrala, Dawid; Kaczmarzyk, Marek (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2022)
Entering the 21st century coincided with a serious crisis of the school. Among many problems that are noticed and diagnosed against the educational environment and the school as an institution, the most important problem is the limits of responsibility for the effect of the raising process. The most visible symptom in this case is the worsening quality of the relationship between parents and their children’s teachers. The article is an attempt to interpret the basis of this phenomenon both from the perspective of contemporary challenges and the foundations of the educational process related to the evolution of our species. The authors try to describe the limits of possibilities and responsibility, they also point out the complexity of factors influencing raising as a source of misunderstandings between people representing the environments of the family home and school. The authors also propose a change of perspective allowing for a different interpretation of these misunderstandings.